Single-pill combination therapy is the standard of care for hypertension, but it is time for the next step: Implementation - Jose P. Lopez-Lopez; LOPEZ JARAMILLO, JOSÉ PATRICIO (Elsevier BV, 2024)
The GMRx2 trial1 in adults with high blood pressure (BP) demonstrated that after 12 weeks, a low-dose single-pill combination of telmisartan, amlodipine, and indapamide significantly reduced BP levels compared to several dual combinations (telmisartan with amlodipine, telmisartan with indapamide, or amlodipine with indapamide). Adverse events did not differ between the groups. This novel therapeutic option could improve high BP control
Keywords: Amlodipine; Antihypertensive Agents; Benzimidazoles; Benzoates; Drug Combinations; Humans; Hypertension; Indapamide; Standard of Care; Telmisarta